A Review of Big Data Resource Management: Using Smart Grid Systems as a Case Study. (22nd October 2021) - Khan, Muhammad Fawad; Azam, Muhammad; Khan, Muhammad Asghar; Algarni, Fahad; Ashfaq, Mujaddad; Ahmad, Ibtihaj; Ullah, Insaf
Abstract : Big data has recently been a prominent topic of research due to the exponential growth of data every year. This massive growth of data is causing problems with resource management. The available literature does not address this problem in depth. Therefore, in this article, we aim to cover the topic of resource management for big data in detail. We addressed resource management from the perspective of smart grids for a better understanding. This study includes a number of tools and methods, such as Hadoop and MapReduce. Large data sets created by smart grids or other data-generating sources may be handled using such tools and approaches. In this article, we also discussed resource management in terms of various vulnerabilities and security risks to data and information being transmitted or received, as well as big data analytics. In summary, our comprehensive study of big data in terms of data creation, processing, resource management, and analysis gives a full picture of big data.